2021
DOI: 10.3390/lubricants9040035
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and Competitive Effects between Zinc Dialkyldithiophosphates and Modern Generation of Additives in Engine Oil

Abstract: The increasing demand for low-viscosity engine oil has underscored the role of zinc dialkyldithiophosphates (ZDDP) as a conventional anti-wear and antioxidant additive. It is essential to investigate the influence of modern additives such as cyclopropanecarboxylic acid (CPCa) and Ni nanoparticles on the tribological performance of ZDDP for practical commercial oil application. According to the experimental results, Ni nanoparticles formed a protective film that exhibited a synergistic effect with ZDDP. A signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…The tribological tests were carried out using a TRB 3 tribometer. The ball-on-disc configuration operated at a humidity of 37 ± 15% and an ambient temperature (T 0 ) of 24 ± 4 • C. The test parameters were as follows: load 10 N, sliding speed 0.1 m/s and sliding distance 1000 m.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tribological tests were carried out using a TRB 3 tribometer. The ball-on-disc configuration operated at a humidity of 37 ± 15% and an ambient temperature (T 0 ) of 24 ± 4 • C. The test parameters were as follows: load 10 N, sliding speed 0.1 m/s and sliding distance 1000 m.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most common lubricant additives is zinc dialkyldithiophosphate, ZDDP, added, for instance, to engine oils. Originally, in 1940 [3], it was developed as an antioxidant and detergent [4]; its other potential applications were suggested later [3]. In the literature, ZDDP is classified as an antiwear and anticorrosion additive [5].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, to the best of the authors' knowledge, there was no peer-reviewed reference about MC performance in powertrains, even though that is its primary application. Contrastingly, there are thousands of papers evaluating the performance of base or fully formulated oils with the addition of additives or nanoparticles using standardized and tribological tests [11,[18][19][20][21][22]. Although lab tests (pin-on-disk, four-ball, copper corrosion, etc.)…”
Section: Additivesmentioning
confidence: 99%
“…Although lab tests (pin-on-disk, four-ball, copper corrosion, etc.) provide evidence and insights into lubricants' performance, it is challenging to evaluate engine conditions in the laboratory [18,22,23]. In fact, it has been shown that elaborate tests fail to reproduce the tribofilms observed in engine parts [18,21].…”
Section: Additivesmentioning
confidence: 99%
See 1 more Smart Citation